Migration and hybrid political regimes : navigating the legal landscape in Russia - Urinboyev, Rustamjon (University of California Press, 2021)
"While migration has become an all-important topic of discussion around the globe, mainstream literature on migrants' legal adaptation and integration has focused on case studies of immigrant communities in Western-style democracies. We know relatively little about how migrants adapt to a new legal environment in the ever-growing hybrid political regimes that are neither clearly democratic nor conventionally authoritarian. This book takes up the case of Russia-an archetypal hybrid political regime and the third largest recipients of migrants worldwide-and investigates how Central Asian migrant workers produce new forms of informal governance and legal order. Migrants use the opportunities provided by a weak rule-of-law and a corrupt political system to navigate the repressive legal landscape and to negotiate-using informal channels-access to employment and other opportunities that are hard to obtain through the official legal framework of their host country. This lively ethnography presents new theoretical perspectives for studying immigrant legal incorporation in similar political contexts"--